Microstructural characterisation of ZnO nanoparticles using X-ray peak profile analysis- a comparative study - Maryam Akhwater (المجلة الليبية للدراسات الأكاديمية المعاصرة, 2025)
The applicability of semiconductor crystalline nanomaterials in a wide range of highly performed novel devices is influenced by their microstructural properties. The estimation of these microstructural parameters, including crystallite size, lattice strain, stress, energy density, and lattice parameters has been most frequently carried out using X-ray diffractometry (XRD). In the present work, the crystalline structure of ZnO nanoparticles (ZnO-NPs) was investigated through X-ray peak profile analysis by applying different integral breadth techniques. Therefore, the reliability of different methods namely, the Williamson-Hall (W-H) models which are the uniform deformation model (UDM), the uniform stress deformation model (USDM), and the uniform deformation energy density model (UDEDM), as well as the Halder-Wagner method and the size strain plot Method (SSP) were investigated and compared. In addition, scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDXA) were used to characterize the morphology and chemical structure of synthesized ZnO-NPs. The findings obtained revealed that the lattice strain of the ZnO-NPs estimated from W-H analysis and the SSP method were highly intercorrelated, while the crystallite size calculated from W-H models was almost similar and in better agreement with the previously reported TEM results.